2015
DOI: 10.3389/fphys.2015.00328
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Regulates Acid Secretion of H+-ATPase-rich Ionocytes in Zebrafish (Danio rerio) Embryos

Abstract: Systemic acid-base regulation is vital for physiological processes in vertebrates. Freshwater (FW) fish live in an inconstant environment, and thus frequently face ambient acid stress. FW fish have to efficiently modulate their acid secretion processes for body fluid acid-base homeostasis during ambient acid challenge; hormonal control plays an important role in such physiological regulation. The hormone cortisol was previously proposed to be associated with acid base regulation in FW fish; however, the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…Similar to some other freshwater species, exposure of zebrafish to cortisol stimulates the uptake of both Na + and Ca 2+ (Kumai et al, 2012a;Lin et al, 2016;Lin et al, 2011), and the secretion of H + (Lin et al, 2015). Using in situ hybridization or immunohistochemistry, the glucocorticoid receptor (GR) was found to be expressed in NaRCs (Cruz et al, 2013), HRCs (Kumai et al, 2012a) and NCCCs (Lin et al, 2016) in zebrafish.…”
Section: Cortisolmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to some other freshwater species, exposure of zebrafish to cortisol stimulates the uptake of both Na + and Ca 2+ (Kumai et al, 2012a;Lin et al, 2016;Lin et al, 2011), and the secretion of H + (Lin et al, 2015). Using in situ hybridization or immunohistochemistry, the glucocorticoid receptor (GR) was found to be expressed in NaRCs (Cruz et al, 2013), HRCs (Kumai et al, 2012a) and NCCCs (Lin et al, 2016) in zebrafish.…”
Section: Cortisolmentioning
confidence: 94%
“…Using in situ hybridization or immunohistochemistry, the glucocorticoid receptor (GR) was found to be expressed in NaRCs (Cruz et al, 2013), HRCs (Kumai et al, 2012a) and NCCCs (Lin et al, 2016) in zebrafish. Exposure to cortisol was also shown to increase mRNA expression of genes that are involved in ion uptake or H + secretion, including ecac, ncc, nhe3b, atp6v1a, ae1b, ca2-like a, and ca15a (Lin et al, 2015;Lin et al, 2011).…”
Section: Cortisolmentioning
confidence: 95%
“…Isotocin, prolactin, and cortisol enhance the expression of ncc2b via the upregulation of cell differentiation in zebrafish [14,44]. It remains to be established how these hormones work together to regulate the function of NCC2b and other Cl 2 transporters in the context of body fluid Cl 2 homeostasis in different vertebrate species.…”
Section: Discussionmentioning
confidence: 99%
“…According to studies of cell experiments, cortisol is able to stimulate the transcription activity of reporter construct with the teleost glucocorticoid receptor (GR) and mineralcorticoid receptor (MR) [45,46,47,48]. Nevertheless, in vivo study indicated that cortisol regulates body fluid ion homeostasis via GR rather than MR in zebrafish [33,49,50,51,52]. …”
Section: The Regulation Of Ca2+ Uptake In Zebrafishmentioning
confidence: 99%